(untitled) (Research, Society and Development, 2022)
Introduction: Health professionals have undergone a profound change in their work to combat the COVID-19 pandemic, which has led to a potential psychological and emotional impact on this population. None of the systematic reviews that evaluated the mental health of these professionals specifically addressed physical therapists. Objective: To identify mental health risks in physical therapists, and personal and systemic factors that increase their vulnerability. Methods: Systematic review performed according to Cochrane guidelines. A systematic search was performed between October 2021 and January 2022, in the following databases: CENTRAL, ClinicalTrials.gov, WHO ICTRP, SCIENCE DIRECT, Google Scholar, SCIELO, LILACS, PUBMED/MEDLINE and bioRxiv/medRvix, for works published between 2020 and 2021. Full-text studies were considered, published or not, in any language, in any location, evaluating the impacts of mental health exclusively on physical therapists, during the pandemic. The methodological quality of the articles was evaluated using the Risk of Bias (RoB) tool using the RevMan 5.4.1 software. Results and Discussion: After searching and analyzing the eligibility criteria, 8 articles were included for qualitative analysis. All of them were cross-sectional studies, exclusively with physical therapists. The sample size was 1007 physical therapists. Conclusion: The COVID-19 pandemic increased the incidence of anxiety, depression, stress, changes in sleep and quality of life, changes in emotion and feelings, psychological distress, post-traumatic disorder and Burnout in physical therapists. However, more robust studies, and directed to the population of physical therapists, are necessary to increase the level of evidence of the study in question.